Upaya Peningkatan Penjualan Produk Batu Bata di Desa Kuto Sari Kecamatan Belitang III Kabupaten Ogan Komering Ulu Timur - Helisia Margahana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Efforts to increase sales is a way that can be done to increase production which will be accompanied by increased revenue, increased profits or profits. There are many ways you can do to increase sales including disseminating information through promotions, price discounts, improving product quality, collaborating with other parties. Kutosari Village is one of the villages in the East OKU Regency, Belitang III District. One of the residents' livelihoods is as a brick maker. In addition to raw materials that are easily obtained, brick making has become the expertise of most residents, because the production of these bricks has been carried out for generations. So far, the marketing of bricks in the village of Kuto Sari is done by sellers who only place their products in front of their homes, waiting for consumers to come to the brick production site themselves. Therefore, the marketing of bricks must be increased in a more vigorous way through promotion through social media, online, coming to building shops to collaborate and many other things in order to increase sales of brick products to be achieved in the village of Kuto Sari.